2019
DOI: 10.21203/rs.2.17150/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burden of cervical lesion in Ethiopia: Systematic review and meta-analysis

Abstract: Though cervical cancer is largely preventable, it is still the second most common female cancer globally and the leading cause of cancer deaths among females in African. Though many efforts has been done to study the burden of the disease in Ethiopia, there are still fragmented primary studies reported cervical lesion. Hence, this systematic review and meta-analysis aimed in estimating the pooled prevalence of cervical cancer and its trend in Ethiopia. Methods: This systematic review and meta-analysis was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…5,6 A meta-analysis study in Ethiopia revealed that one among six of the study participants had a cervical lesion. 10 Given the limited available data, the prevalence and death rate may be even higher than the number reported. 11 Cancer of the cervix is a highly preventable disease through HPV vaccination and cytological screening programs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 A meta-analysis study in Ethiopia revealed that one among six of the study participants had a cervical lesion. 10 Given the limited available data, the prevalence and death rate may be even higher than the number reported. 11 Cancer of the cervix is a highly preventable disease through HPV vaccination and cytological screening programs.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, a total of 22,818 women aged 30-49 undergone cervical cancer screening in 2015. 16,17 Even though early cervical screening and detection are the most effective approach to prevent cervical cancer, the trend of cervical lesion was in increasing fashion. Moreover, as far as our level of knowledge there is no study done among women of 30-65 years where the prevalence of the problem is more prominent.…”
Section: Introductionmentioning
confidence: 99%